Rate and determinants of low fifth minute Apgar score at the federal medical centre Yenagoa, Bayelsa State, Nigeria - Makinde, Olakunle I.; Awotundun, Benjamin O.; Osegi, Nkencho (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: About a quarter of neonatal deaths and about 10% of deaths of children under 5 years are due to intrapartum related events reflected as low fifth minute Apgar score. This study is to assess the rate of low fifth minute Apgar score and its determinants at the Federal Medical Centre Yenagoa, Bayelsa State, Nigeria. Methods: A cross-sectional study of births at the Federal Medical Centre Yenagoa between July 2020 and April 2021. Data was collected in real time from parturients’ case notes at delivery. Low fifth minute Apgar score was defined as Apgar score < 7 at the 5th minute of birth. Data was analysed using IBM SPSS Statistics version 23. Multivariate logistic regression was used to identify determinants of low fifth minute Apgar score. P Value was 0.05. Results: Rate of low fifth minute Apgar score was 16.6%. Unbooked status (OR - 2.29; CI-1.11 - 4.71; p value - 0.024), emergency caesarean section (OR - 10.44; CI - 1.10 - 99.26; p value - 0.041), urgent caesarean section (OR - 25.75; CI - 2.58 – 256.72; p value=0.006) and breech presentation (OR - 1.96; CI - 1.03 – 3.82; p value=0.049) significantly increased the odd of low fifth minute Apgar score. Conclusions: Unbooked status, emergency and urgent caesarean section, and breech presentation were the determinants of low fifth minute Apgar score in the population studied. This highlights the patient group and clinical scenario requiring a focus of intervention for prevention of morbidity and mortality from low fifth minute Apgar score.